Refleksi Pelaksanaan Pilkada Serentak 2020: Suatu Kajian Tentang Demokrasi di Indonesia - Igam Arya Wada (Fakultas Hukum Universitas Surabaya, 2022)
In 2020, Indonesia is mandated by Law No. 10 of 2016 on the second amendment to Law No. 1 of 2015 on the Election of Governors, Regents, and Mayors to conduct simultaneous elections. But on the other hand, the Government of Indonesia also has a policy in an effort to control cases of the Covid-19 pandemic in Indonesia by limiting people to gather. This is a dilemma, that the key to the success of the election is one of them is seen from the level of participation of the people who attended to vote. However, this is doubtful considering that the public still has fears of being exposed to the covid-19 virus. Thus, this article aims to see the success of the implementation of the Sentak Election in 2020 judging from the aspect of democracy, especially public participation. In an effort to achieve this goal, this article was written with literature research that emphasizes the legislative approach and conceptual approach. Therefore, this article concludes that the implementation of simultaneous elections in 2020 still presents many problems in various aspects and still many received rejection from the public, so that it has an impact on the level of participation.